Employment Arrangement for Person with Disabilities in Indonesia in Post-New Order Era - Dewi W, Imma Indra (Universitas Muhammadiyah Yogyakarta, 2019)
The right to employment of persons with disabilities got better attentions in Indonesia, especially after the fall of the New Order era. This paper discusses the employment arrangement for persons with disabilities in Indonesia in Post-New Order era. It is found that some reforms have been made to accealerate the fulfillment of the right to employment of persons with disabilities. It began with the enactment of Law Number 21 of 2002 on Labour Union and Law Number 13 of 2003 on Employment. In addition, the Government had ratified the Convention on the Rights of Persons with Disabilities through Law Number 19 of 2011. Furthermore, Law Number 8 of 2016 on Person with Disabilities was issued. This law has properly regulated the rights of persons with disabilities, including their employment rights. Nevertheless, this law still requires several comprehensive operational regulations. Law Number 13 of 2003 can be synchronized with Law Number 8 of 2016 since it functions as a guideline for employers and workers in carrying out working relationship.